NMDA receptors in neurodegenerative diseases: mechanisms and emerging therapeutic strategies - Zhang, Keyi; Wen, Ming; Nan, Xinyue; Zhao, Shuaizhu; Li, Hao; Ai, Yanping; Zhu, Houze (Frontiers in Aging Neuroscience, 2025)
NMDA receptors (NMDARs) are widely distributed throughout the central nervous system (CNS) and play pivotal roles in normal physiological processes such as synaptic plasticity, learning, and memory. Substantial evidence indicates that NMDAR dysfunction, particularly excessive calcium influx, critically contributes to the pathogenesis of major neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS). Dysregulated glutamatergic signaling synergizes with pathological protein aggregation (e.g., Aβ, α-synuclein, mutant huntingtin) to drive neuronal loss. We systematically delineate NMDAR-related mechanisms underlying neurodegeneration, highlighting spatial-specific roles (e.g., synaptic NMDAR-mediated neuroprotection versus extrasynaptic NMDAR-mediated excitotoxicity) and crosstalk with mitochondrial dysfunction and oxidative stress. We critically evaluate current therapeutic strategies targeting NMDARs, including subunit-selective modulators, downstream effector modulation, and glutamate transporter modulation designed to restore NMDAR homeostasis. Consequently, NMDARs and their modulators represent promising therapeutic targets for these refractory conditions. This review comprehensively summarizes current research on the involvement of NMDARs and the glutamatergic system in neurodegenerative diseases. Furthermore, we discuss the clinical application of NMDAR-targeting agents and explore emerging therapeutic strategies focused on modulating NMDAR-related pathways. This article aims to provide a reference for elucidating the molecular mechanisms underlying these neurodegenerative disorders and to highlight potential avenues for future drug development.